RELATIONSHIP BETWEEN GADGET USE INTENSITY AND DEPRESSION LEVEL IN STUDENTS OF SMA NEGERI 5 MAKASSAR CITY - Andi Nurul Mawaddah BN; Trisnawaty; Delima, Andi Alifia Ayu; Annisha, Fhirastika; Dahlan M (Bina Generasi : Jurnal Kesehatan, 2025)
Background: Gadgets have become a major necessity for interaction in the technological era with both positive and negative impacts. Excessive use can lead to mental health problems, one of which is depression. Adolescents are subjected to technological developments during their transition period so they are more vulnerable to these negative impacts. Objective: This study aims to determine the relationship between the intensity of gadget use and the level of depression in SMA Negeri 5 Makassar City students. Methods: Cross sectional study at SMA Negeri 5 Makassar City on 208 randomly selected students representing each class. Data were analyzed univariately and bivariately using Spearman's Rho to assess the influence between the independent variable and the dependent variable, and Spearman's Rho correlation to determine the extent of the relationship between the two variables. Results: The intensity of gadget use with the level of depression in SMA Negeri 5 Makassar City students is significantly related, obtained a p value of 0.001 (p≤0.05) with Spearman's Rho correlation showing the relationship coefficient value (r = 0.234), meaning that the level of relationship strength or correlation between the intensity of gadget use and the level of depression is a moderate correlation with a positive correlation direction. Results: The study found a significant relationship between the intensity of gadget use and the level of depression in students of SMA Negeri 5 Makassar City with a positive correlation.